The main role of investment for the entrepreneurship (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
These needs can be attained from the interest obtained by investing the principle amount of the enterprise. This helps the entrepreneur run their personal and professional life simultaneously with ease.